“Técnicas de rehabilitación respiratoria y su influencia en pacientes con enfermedad pulmonar obstructiva crónica atendidas en el hospital de Infectologia De La Provincia Del Guayas periodo primer semestre 2018” - Merelo Ronquillo, Jose Eduardo (2018)
The research project was focused on respiratory therapy as a set of techniques for the treatment of patients with chronic obstructive disease COPD at the Hospital de Infectologia, being a very effective therapy for the control, recovery and reduction of sequelae, without adverse effects and improve your lifestyle. This study aimed to determine the influence of respiratory rehabilitation techniques in patients with chronic obstructive pulmonary disease treated at the infectology hospital in the province of Guayas, first semester 2018; the research problem allowed to direct the study towards new strategies to complement the pharmacological treatment that the patients receive, considering the analysis of the field study, the sample was conformed by 80 patients, to whom the survey was applied to obtain relevant information and values percentage that contributed to the development of a respiratory rehabilitation techniques plan. This proposal specialized in presenting a series of exercises that manage to prevent the decline of biological functions in patients with COPD.